The Impact of Remote Working on Productivity and Work-Life Balance of Millennial Employees in DKI Jakarta - Theresia Agung Maryudi Harsiwi; Malvin Rheza Paleva (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2025)
Objective – This study aims to analyze the effect of remote working on employee productivity and work-life balance among millennial employees in DKI Jakarta. Remote working offers flexibility for employees in managing their work time and personal life, which is expected to increase productivity and work-life balance. Design/Methodology/Approach – This study uses a quantitative design with a purposive sampling method on 105 millennial employees who work remotely in DKI Jakarta. Data were collected through an online survey distributed through the Poplite by Populix platform. Data analysis was carried out using a simple linear regression test to test the effect of remote working on employee productivity and work-life balance. Findings – The results of the study show that remote working has a significant and positive effect on employee productivity, as well as remote working has a significant and positive effect on work-life balance among millennial employees in DKI Jakarta. Implications – The contribution of this study's originality lies in the exploration of the millennial generation who work remotely, which is rarely studied in the context of remote working that is starting to be widely implemented by organizations. Moreover, it is supported by the characteristics of the millennial generation who are more technologically literate, flexible and adaptive, innovative and independent, prioritize mental and physical health, and prioritize work-life balance. Ultimately, it can provide new insights for the human resources department in responding to the significant increase in the proportion of the millennial generation in the world of work.